Fogging with antibrowning agents as an alternative to conventional immersion treatments to extend shelf life of mushrooms - Ojeda, Gonzalo Adrian (2020)
Mushroom (Agaricus bisporus) is a highly perishable product and can be easily damaged when immersion in antibrowning solutions is performed; therefore, fogging application represents a less aggressive technique.The objective of this work was to evaluate the effect of different antibrowning agents (ascorbicacid, sodium metabisulphite and L-cysteine) applied by two methodologies (immersion and fogging) on the quality of mushrooms during storage at 5 °C. Weight losses, microstructural organisation, colour and texture changes were evaluated as quality indicators. Polyphenol oxidase activity, phenolic content and antioxidant activity were also evaluated. Fogging achieved browning inhibition without major changes in firmness, while immersion treatments inhibited browning but significant changes in firmness were found.Browning inhibition achieved by fogging showed similar results when compared to the conventional immersion treatments. Fogging has the advantage of being less aggressive than immersion while requiring a significantly smaller amount of antibrowning solution than traditional immersion.